2014
DOI: 10.1002/2014gl060818
|View full text |Cite
|
Sign up to set email alerts
|

Lunar gravitational atmospheric tide, surface to 50 km in a global, gridded data set

Abstract: The lunar gravitational semidiurnal atmospheric tide L2 is detected in the geopotential field in the ERA‐Interim reanalysis by regressing the data for each of the four daily analysis times onto periodic lunar half‐synodic cycle time series and differencing the resulting regression maps. A robust pattern dominated by zonal wave number 2 emerges, which agrees with tidal theory and with previous observational studies based on station data in terms of its amplitude, phase, and seasonality at the Earth's surface. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…They are therefore suppressed by the analysis procedure, in particular at locations where δpnormalM2 is effectively out of phase with the uniform westward propagation of the dynamic L 2 tide. Based on these anomalies, Kohyama and Wallace [] have suggested that also the zonally varying structures of L 2 in the Tropics are repercussions of the ocean tidal lifting effect. Our results (Figure a) question that view; the separation into five regional maxima is a distinct characteristic of the crust‐referred tide, and even for reanalyses the impact of δpnormalM2 from vertically displaced marine sensor data appears to be minimal in latitudes below 30°.…”
Section: Validation Of L2 In Global Reanalysesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are therefore suppressed by the analysis procedure, in particular at locations where δpnormalM2 is effectively out of phase with the uniform westward propagation of the dynamic L 2 tide. Based on these anomalies, Kohyama and Wallace [] have suggested that also the zonally varying structures of L 2 in the Tropics are repercussions of the ocean tidal lifting effect. Our results (Figure a) question that view; the separation into five regional maxima is a distinct characteristic of the crust‐referred tide, and even for reanalyses the impact of δpnormalM2 from vertically displaced marine sensor data appears to be minimal in latitudes below 30°.…”
Section: Validation Of L2 In Global Reanalysesmentioning
confidence: 99%
“…After curtailing the spectrum to s = 2, we deduced latitudinal profiles of amplitude and phase ( ϕ ) variations. The conversion of phase lags on the equilibrium tide to local lunar time of maximum pressure T max (in lunar hours) reads [ Kohyama and Wallace , ] Tmax=240.3emnormallunarhours4π()ϕ+2λ. …”
Section: Validation Of L2 In Global Reanalysesmentioning
confidence: 99%
“…Dai and Wang, 1999;Schindelegger and Ray, 2014) and lunar tides (e.g. Kohyama and Wallace, 2014;Schindelegger and Dobslaw, 2016) at ground level would be a valuable application of the IMS infrasound data. By now, the focus of such empirical models is often limited to the diurnal and the semidiurnal tide.…”
Section: Discussionmentioning
confidence: 99%
“…Near IS27, these excitations amount to about 4 Pa (Schindelegger and Dobslaw, 2016). The open-ocean tide amounts to 0.5 m (Kohyama and Wallace, 2014). To a certain extent, the Ekstroem Ice Shelf moves with the ocean tide which may enhance the barometric effect of the lunar tide as the vertical movement translates into a barometric signal.…”
Section: The Lunar Tidesmentioning
confidence: 99%
“…Hsu and Hoskins (1989) and Kohyama and Wallace (2014) derived S 2 migrating tides in the stratosphere by using the ECMWF operational analysis and the ERA-Interim, respectively. Li et al (2015) used CFSR reanalysis to examine the seasonality of S 2 migrating tides.…”
mentioning
confidence: 99%